Serum cross-linked n-telopeptides of type 1 collagen (NTx) in patients with solid tumors - Jablonka, Fernando (2009)
CONTEXT AND OBJECTIVE: Cross-linked N-telopeptides of type I collagen (NTx) increase in concentration in situations in which bone resorption is increased, such as osteoporosis and bone metastasis (BM). We aimed to evaluate the serum concentrations of NTx in a sample of patients with several types of solid tumors. DESIGN AND SETTING: Cross-sectional analytical study with a control group in a tertiary public hospital. METHODS: We performed the quantitative enzyme-linked immunosorbent assay (ELISA) on serum NTx levels in 19 subjects without a history of cancer and 62 patients with various solid tumors who had been referred for a bone scan. Three experienced analysts read all bone scans. RESULTS: The serum NTx levels in patients with cancer and BM, with cancer but without BM and without cancer were 46.77 ± 2.58, 32.85 ± 2.05 and 22.32 ± 2.90 respectively (P < 0.0001). We did not find any significant correlations of serum NTx with age, gender, history of bone pain, tumor type and bone alkaline phosphatase levels. We found a significant correlation between serum NTx and alkaline phosphatase levels (R2 = 0.08; P = 0.022). CONCLUSIONS: Serum NTx levels are significantly higher in patients with solid tumors and bone metastases than they are in patients without bone metastases and in normal controls.